UiTM vehicle sticker system / Mohd Sharil Abdul Hamid - Mohd Sharil, Abdul Hamid (Faculty of Computer and Mathematical Sciences, 2007)
Universiti Teknologi MARA (UiTM) vehicle sticker is important to trace out the valid or invalid vehicles to enter UiTM. UiTM staffs, students and UiTM non-staff (user), who have a vehicle and qualify, need to register their vehicle and get the UiTM vehicle sticker. The problems are user who qualify, need to fill in the form manually and it takes time during registration process. An additionally, students who have vehicle summon, need to check their summons at the UiTM security office. UiTM Vehicles Sticker System is designed to provide one manageable system that solves registration of vehicles manually. With this system, it helps users to register fast and easily. Also, user will be able to check vehicle summons easily online. Furthermore the system are using summon e-mail alert to notify users that have summon. During application process, the system also sends email notification automatically to the UiTM security staff department to notify that they have a new applicant. The UiTM staff security also can manage the registration process and vehicle summons more efficiently. UiTM security staff department also can trace out the vehicle easily. UiTM Vehicle Sticker System is connected with a web-based system. The web-based system is developed with PHP as interface and MySQL as a database. Apache server is needed to store the information and PostCast as a E-mail server. As a conclusion, hopefully with this idea it can make an easy, fast and manageable ways to solve the problems in register vehicles manually. The expected result from this project it can help a security staff to manage their work in efficient and make registration process more easy. It can also make UiTM staffs and students save their time in registration process and they can check their vehicle summon easily.